3.8-μm Mid-Infrared Laser Quasi-Synchronously Pumped by a MOPA Structured Picosecond Yb Fiber Amplifier With Multi-pulse Operation - Kaihua Wei; Xuefang Zhou; Xiaomin Lai (IEEE Photonics Journal)
A picosecond pulsed mid-infrared laser with multi-pulse operation is experimentally demonstrated. This mid-infrared laser was composed of a fiber laser pumped optical parametric oscillator (OPO). The pump source of this OPO was a master oscillator power amplification-structured picosecond fiber amplifier with pulse bunch output, which was further used to quasi-synchronously pump a periodically poled magnesium-oxide doped lithium niobate crystal based OPO to obtain 3.8-μm wavelength output with picosecond multi-pulse operation. The pump-idler conversion efficiency, the signal spectrum, and the signal pulse bunch are presented, respectively.